The Use of Group Work Methods and Picture Media to Improve Thematic Learning Outcomes of My Daily Assignment Themes (Penggunaan Metode Kerja Kelompok Dan Media Gambar Untuk Meningkatkan Hasil Belajar Tematik Tema Tugasku Sehari-Hari) (Shautut Tarbiyah, 2023)
This article describes the use of group work methods and media images in increasing thematic learning outcomes with the theme of my daily assignments. The research was conducted at SDN 92 Kendari using a classroom action research approach. The research subjects were students of class II semester I, totaling 26 students. Preliminary research shows that teachers have made various efforts to improve thematic learning outcomes. These efforts include: giving LKS (student worksheets), practice questions, and homework. However, these efforts have not been able to improve student thematic learning outcomes. This becomes the basis for the application of group work methods and media images to improve thematic learning outcomes. Based on the results of the research that has been carried out, it can be concluded as follows: Students become more enthusiastic and motivated in learning thematic. In class II semester I SD Negeri 92 Kendari, totaling 26 students, it turned out that from cycle to cycle, student learning outcomes increased. From 21.74% of students who completed it to 73.46% in cycle 1, then in cycle 2 it increased to 96.15%. By applying the Group Work Method and Image Media in learning, it can improve the learning outcomes of class II students in the odd semester of SD Negeri 92 Kendari for the 2019/2020 academic year, with a completeness percentage of 96.15%.Keywords:     Group Work Methods, Image Media, Learning Outcomes